Intertwined between Samawi Religions (Islam-Christianity) and the Cosmology of the Naulu People - Tuahuns, Fitrawati; Watloly, Aholiab; Wakano, Abidin (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
This research was conducted within the religious context of one of the indigenous tribes in Maluku, located in Siwalalat District, Central Maluku. This research examines the social changes in the spiritual patterns of the Naulu people following their adoption of the Abrahamic religions, specifically Islam and Christianity. Using qualitative research methods, this study aims to observe and understand the phenomenon of social change in the religious patterns of the Naulu Tribe after they adopted the Abrahamic religion, and to analyze it with a scientific approach, resulting in academic findings. The study's results show that the presence of the Abrahamic religions has altered the pattern of faith and community life. There is a process of growth and development of new cultures, new ways of life, and new mindsets in appreciating various values, including the influence of money, goods, education, and strong government politics. However, the Naulu people still maintain their traditional values, such as living simply, wearing cloth tied around their heads, and living dependent on forests and customary land as a true and fundamental way of life. They still hold fast to the traditional belief that land and forests are the cosmos of the original Naulu people. It is in the forests and customary land that they maintain the integrity of the Naulu Tribe's life, which is always connected to their ancestors. This finding represents the connection between the Samawi religion and the local cosmology of the Naulu people, which must be preserved as a contextual aspect of their religion.